New thinking on gonorrhoea control in MSM: are antiseptic mouthwashes the answer?. Issue 1 (February 2018) - Fairley, Christopher K.; Zhang, Lei; Chow, Eric P.F.
Abstract : Purpose of review: The rate of gonorrhoea is rising and is much higher in men who have sex with men (MSM) than heterosexuals. The purpose of this review was to describe research supporting a new paradigm of transmission of gonorrhoea in MSM and interventions that may result from this. Recent findings: Evidence is accumulating that gonorrhoea in MSM is transmitted differently than previously thought and that asymptomatic sites of infection may play a major role in the persistent of gonorrhoea at a population level. Saliva commonly contains gonorrhoea, and saliva is commonly used during sexual acts. Both in-vitro, in-vivo studies have suggested that antibacterial mouthwash may reduce gonorrhoea at the oropharynx. A recently published mathematical model also suggests that if mouthwash were effective, it would result in considerable declines in the community prevalence in MSM. Summary: A newly suggested paradigm for the transmission of gonorrhoea in MSM could potentially offer a simple condom-free control strategy. But considerable more research is required before it could be recommended even if it were shown to be effective in a clinical trial.